In Search for the Links Between History and Sociology - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 2001)
Foreword: A special issue of “Sociologija. Mintis ir veiksmas” contains a number of original papers presented at the conference “The Developments of Identity: History and Present“ (a section of the international conference “Transformations in the Eastern and Central Europe“), organized by the Department of History of Klaipėda University and the Department of Sociology of Vilnius University in Klaipėda (2001-05-26).